Senior universities - Portuguese legal framework - Tavares, Sandra (2017)
This article intends to present some fundamental documents, from international organizations and from the Portuguese government, establishing the importance of lifelong learning, purpose that can be achieved, for instance, with the support of senior universities. Promote lifelong learning in particular for seniors is one of the three objectives stated for the International Scientific Conference of Educational Projects for Seniors by its organization.